2022
DOI: 10.1021/acsami.1c19064
|View full text |Cite
|
Sign up to set email alerts
|

Recent Applications of Langmuir–Blodgett Technique in Battery Research

Abstract: The Langmuir–Blodgett (LB) technique, in which monolayers are commonly transferred from a liquid/gas interface to a solid surface, allows convenient fabrication of highly ordered thin films with molecular-level precision. This method is widely applicable to substances ranging from organic molecules to nanomaterials. Therefore, LB methods have provided a critical toolbox for researchers to engineer nanoarchitectures. The LB fabrication process is also compatible with numerous substrate materials over large area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Nanoarchitectonics is particularly suited for the fabrication of hierarchical structures because it combines processes that include not only the self-assembly of components but also human manipulation, such as the Langmuir–Blodgett (LB) method, 29 layer-by-layer (LbL) assembly, 30 and various microfabrication methods. 31 The high capability of nanoarchitectonics for the fabrication of hierarchical functional structures 32 shares features of structural constructions seen in biological systems in which huge numbers of functional components are hierarchically organized and their functions are linked together.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoarchitectonics is particularly suited for the fabrication of hierarchical structures because it combines processes that include not only the self-assembly of components but also human manipulation, such as the Langmuir–Blodgett (LB) method, 29 layer-by-layer (LbL) assembly, 30 and various microfabrication methods. 31 The high capability of nanoarchitectonics for the fabrication of hierarchical functional structures 32 shares features of structural constructions seen in biological systems in which huge numbers of functional components are hierarchically organized and their functions are linked together.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of sensors, it has been reported that organized and ultrathin nature of LB films of materials can offer a large enhancement in sensing parameters as compared to randomly oriented thick films [19,20]. The LB films can be used for non-linear optical devices, photovoltaics, ultrafiltration membrane, molecular electronic, and energy storage devices [21][22][23]. The shapeanisotropic liquid crystal molecules at the air-water interface show very interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their wide range of possible applications in modified electrodes [3], batteries [4], and solar devices [5], extremely thin and highly structured organicinorganic films built on solid substrates have garnered considerable attention in recent decades. Layer-bylayer structural ordering is beneficial for enhancing charge carrier mobility [6].…”
Section: Introductionmentioning
confidence: 99%